Dwelling in Software: Aspects of the felt-life of engineers in large software projects - Harper, Richard; Bird, Christian; Zimmermann, Tom; Murphy, Brendan (E-CSCW, 2014)
The organizational and social aspects of software engineering (SE) are now increasingly well investigated. This paper proposes that there are a number of approaches taken in research that can be distinguished not by their method or topic but by the different views they construct of the human agent acting in SE. These views have implications for the pragmatic outcome of the research, such as whether systems design suggestions are made, proposals for the development of practical reasoning tools or the effect of Social Network Systems on engineer’s sociability. This paper suggests that these studies tend to underemphasize the felt-life of engineers, a felt-life that is profoundly emotional though played out in reference to ideas of moral propriety and ethics. This paper will present a study of this felt-life, suggesting it consists of a form of digital dwelling. The perspective this view affords is contrasted with process and ‘scientific’ approaches to the human agent in SE, and with the more humanistic studies of SE reasoning common in CSCW.